Proceedings of the Web Conference 2021 2021
DOI: 10.1145/3442381.3450019
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Softening Can Lead to Hardening of Opinions: Evidence from a Randomized Controlled Trial

Abstract: Motivated by the goal of designing interventions for softening polarized opinions on the Web, and building on results from psychology, we hypothesized that people would be moved more easily towards opposing opinions when the latter were voiced by a celebrity they like, rather than by a celebrity they dislike. We tested this hypothesis in a survey-based randomized controlled trial in which we exposed respondents to opinions that were randomly assigned to one of four spokespersons each: a disagreeing but liked c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…1.25) for Human-Human debates. This trend is consistent with previous literature describing a hardening of pre-treatment opinions when people express their ideas [75] or are exposed to disagreeing views [76], or finding opinion change to be highly affected by argument order [77].…”
Section: Should Every Citizen Receive a Basic Income From The Governm...supporting
confidence: 92%
“…1.25) for Human-Human debates. This trend is consistent with previous literature describing a hardening of pre-treatment opinions when people express their ideas [75] or are exposed to disagreeing views [76], or finding opinion change to be highly affected by argument order [77].…”
Section: Should Every Citizen Receive a Basic Income From The Governm...supporting
confidence: 92%
“…In contrast, Guess and Coppock (2020) run a series of survey experiments exposing participants to opposing views but find no evidence of "backfire" effects. A recent study by Spitz et al (2021) that focuses on the identity of the source of opposing views provides some insights on when "backfire" effects are more likely to occur.…”
Section: Randomized Experiments To Understand Polarizationmentioning
confidence: 99%
“…The results obtained in [16] showed confirmation bias in combination with the backfire effect to be strong drivers of polarization. The authors in [133] showed evidence of polarization development in another combination of PSOC constructs: parasocial relationships and HOMY. It was shown that people became further entrenched in their preconceived beliefs in the case of a contradicting opinion from a subject matter expert celebrity.…”
Section: Polarization Dimension As Shown In Tablementioning
confidence: 99%